The Bioavailability and Evolution of Trace Metals in Environment: A Brief Review - Hui Zhang (The Global Environmental Engineers, 2016)
As a kind of important pollutants, trace metals and the pollution have been become a concerned worldwide environmental problem. Despite the fact that the bioavailability of trace metals indicated by their speciation has been an indispensible parameter in the assessment and treatment of trace metal pollution, many studies suggest that the bioavailability of trace metals may change according to environmental conditions, and they can also transform between some speciation fractions. These transformations are related with factors such as the compositions, microorganism, time, and other physical-chemical conditions of the system. So, it is necessary to systematically understand and investigate for the factors to affect the transformation aside from analysis at certain time-place. The results of these understanding and investigations can be used for reasonably determining the allocation of financial and technical resources in natural and engineered processes with bringing about inspirations from the evolution of the speciation of the trace metals on environmental impacts.